2021
DOI: 10.3389/fevo.2021.630397
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome in Death and Beyond: Current Vistas and Future Trends

Abstract: Forensic medicine has, for a long time, been relying on biochemical, anthropologic, and histopathologic evidences in solving various investigations. However, depending on the method used, lengthy sample processing time, scanty sample, and less sensitivity and accuracy pervade these procedures. Accordingly, newer arenas such as the thanatomicrobiome have come forward to aid in its quandaries; furthermore, the parallel advances in genomic and proteomic techniques have complemented and are still emerging to be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 173 publications
0
26
0
2
Order By: Relevance
“…The HPM became increasingly different from starting communities over time in the internal organs as well as at skin sites, as observed in other reports [ 9 , 10 ]. In previous studies Proteobacteria abundance has been found to increase overall throughout decomposition in animal and human models while Firmicutes and Bacteroidetes decrease [ 42 , 43 ]. Such expected shifts in the structure of the culturable bacterial community over decomposition is also detectable by MALDI-TOF but depends on the anatomical site and insect colonization [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HPM became increasingly different from starting communities over time in the internal organs as well as at skin sites, as observed in other reports [ 9 , 10 ]. In previous studies Proteobacteria abundance has been found to increase overall throughout decomposition in animal and human models while Firmicutes and Bacteroidetes decrease [ 42 , 43 ]. Such expected shifts in the structure of the culturable bacterial community over decomposition is also detectable by MALDI-TOF but depends on the anatomical site and insect colonization [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The natural fluctuations in the number and types of microorganisms associated with a cadaver have great potential to be harnessed for the development of precise and accurate methods for estimation of the PMI [33][34][35][36]. Currently, PMI is generally estimated based on changes to the body, including cooling, lividity, and rigor mortis, followed by gross morphological changes.…”
Section: The Human Postmortem Microbiomementioning
confidence: 99%
“…Organ thanatomicrobiome analyses suggest that facultative anaerobes, such as Lactobacillus, predominate in the "short PMI" timeframe, while in a "long PMI" timeframe a predominance of obligate anaerobes like Clostridium is observed [53]. Notably, Firmicutes (e.g., Clostridium, Peptoniphilus, and Bacillus) represent a stable and constant biomarker in microbial communities derived from different body locations [33]. Even the manner of death (natural, accidental, suicide, homicide, undetermined) has been shown to influence the thanatomicrobiome in various organs [33,39,52].…”
Section: The Human Postmortem Microbiomementioning
confidence: 99%
“…The onset of fluid-filled blisters on the skin and skin slippage, in which huge sheets of skin slough off the body, are the initial signs. (Roy et al, 2021) However, the body has adjusted to its surroundings (algor mortis), blood has accumulated in the body, generating skin darkening (livor mortis), and Because of the increasing alkalinity, the cytoplasm of cells has dissolved (rigor mortis). When a large enough number of cells burst, nutrition fluids emerge available, and the putrefaction might occur (Vass, 2001).…”
Section: Issn: 2767-2972 Backgroundmentioning
confidence: 99%